2019
DOI: 10.1016/j.molcel.2019.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Xist Deletional Analysis Reveals an Interdependency between Xist RNA and Polycomb Complexes for Spreading along the Inactive X

Abstract: During X-inactivation, Xist RNA spreads along an entire chromosome to establish silencing. However, the mechanism and functional RNA elements involved in spreading remain undefined. By performing a comprehensive endogenous Xist deletion screen, we identify Repeat B as crucial for spreading Xist and maintaining Polycomb repressive complexes 1 and 2 (PRC1/PRC2) along the inactive X (Xi). Unexpectedly, spreading of these three factors is inextricably linked. Deleting Repeat B or its direct binding partner, HNRNPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
175
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(212 citation statements)
references
References 81 publications
16
175
0
1
Order By: Relevance
“…4b). The eCLIP sites of human HNRNPK protein, whose mouse homologue mediates recruitment of Polycomb through the B and C regions of mouse Xist 29,38 , closely mirror RNP-MaP site density across the human XIST D region and overlap human XIST B and C regions ( Fig. S8), supporting a model wherein the B, C, and D regions of Xist/XIST are functionally analogous 39 .…”
Section: Rnp-map Identifies Conserved Protein Interaction Network Inmentioning
confidence: 65%
See 1 more Smart Citation
“…4b). The eCLIP sites of human HNRNPK protein, whose mouse homologue mediates recruitment of Polycomb through the B and C regions of mouse Xist 29,38 , closely mirror RNP-MaP site density across the human XIST D region and overlap human XIST B and C regions ( Fig. S8), supporting a model wherein the B, C, and D regions of Xist/XIST are functionally analogous 39 .…”
Section: Rnp-map Identifies Conserved Protein Interaction Network Inmentioning
confidence: 65%
“…Strikingly, regions with high RNP-MaP site density in Xist/XIST corresponded to the A, B, C, D, and E regions ( Fig. 4a), which are each known to contain distinct repetitive sequences important for Xist localization, assembly, and chromatin silencing [28][29][30][31][32][33][34][35] . High RNP-MaP density was observed at each of these repetitive regions despite changes in copy number (human XIST contains two copies of the B region) and changes in size, relative position, and sequence (C, D, and E regions differ extensively between mice and humans) 36 .…”
Section: Rnp-map Identifies Conserved Protein Interaction Network Inmentioning
confidence: 99%
“…22 Another study reported that the repeat B domain within Xist is important for the recruitment and spreading of PRC1 and PRC2 along the Xi and that Xist, PRC1 and PRC2 interdependently regulate X chromosome inactivation. 23 Taken together, these findings prove a clear RNA-mediated function of Xist and establish this lncRNA as an exemplary nuclear RNA that regulates local gene expression.…”
Section: Gene Regulatory Functions Of Lncrna Loci In the Nucleusmentioning
confidence: 72%
“…HDAC3‐mediated histone deacetylation and PRC1‐associated histone H2A ubiquitination have been identified as the earliest chromatin modifications during X chromosome silencing, followed by PRC2‐dependent histone 3 lysine 27 trimethylation (H3K27me3) . Another study reported that the repeat B domain within Xist is important for the recruitment and spreading of PRC1 and PRC2 along the Xi and that Xist , PRC1 and PRC2 interdependently regulate X chromosome inactivation . Taken together, these findings prove a clear RNA‐mediated function of Xist and establish this lncRNA as an exemplary nuclear RNA that regulates local gene expression.…”
Section: Gene Regulatory Functions Of Lncrna Loci In the Nucleusmentioning
confidence: 79%
“…This transcript is expressed from the inactive X chromosome in female cells and coats the Xi chromosome in cis to silence most genes (Galupa & Heard, 2015). XIST RNA is tethered to the Xi chromosome during interphase through a combination of factors including Ciz1 (Ridings-Figueroa et al, 2017;Sunwoo, Colognori, Froberg, Jeon, & Lee, 2017), hnRNP-K (Colognori, Sunwoo, Kriz, Wang, & Lee, 2019;Pintacuda et al, 2017), and hnRNP-U/SAF-A (Hasegawa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%